Peptidoglycan recognition protein PGRP-5 is involved in immune defence and neuro-behavioral disorders in zebrafish embryos - Xi Li; Guanghua Xiong; Manni Luo; Siwan Mao; Ruiying Zhang; Ziwei Meng; Juan Li; Xinjun Liao (PLoS ONE, 2025)
Peptidoglycan recognition proteins (PGRPs) are the evolutionarily highly conserved class of pattern recognition receptors, however, their functions on the innate immune system and neuro-inflammatory response in aquatic organism are still poorly understood. In this study, we systematically investigated the molecular functions of PGRPs in zebrafish embryos. Firstly, we identified three PGRPs in zebrafish and phylogenetic analysis suggested that DrPGRP-5 was a novel member of the PGRP superfamily in evolution. Secondly, the endogenous mRNA levels of DrPGRP-5 were highly expressed in brain and muscle while significantly down-regulated in liver and egg at 72 hpf in zebrafish embryos. Thirdly, the mRNA levels of DrPGRP-5 were greatly elevated after 6 h of E. coli infection but reached its highest value at 24 h after M. luteus stimulation. Moreover, knock-down DrPGRP-5 could significantly reduce the pro-inflammatory cytokines such as TNF-α, IL-1β and IL-6, but increased the expression of anti-inflammatory cytokine TGF-β. On the other hand, the locomotor behavior abilities and the antioxidant enzyme activities such as CAT and SOD were obviously decreased under the DrPGRP-5 KD conditions. Finally, incubation of zebrafish embryos with anti-inflammatory and neuroprotective agents (10 μM Minocycline) can partially rescue the DrPGRP5-regulated locomotor behavior. Taken together, our data suggested that zebrafish PGRP-5 is involved in the innate immune defenses and regulated the neurobehavior and neuro-inflammation, which may provide new strategies for the treatment of neuro-inflammatory diseases in the aquatic organisms.